An improved selective harmonics elimination technique for PV assisted single phase grid-tied PWM inverter. Issue 2 (31st January 2020) - Santra, Subhendu Bikash; Mohanty, Subodh Kumar
Abstract : Purpose: The purpose of this study is to present a new methodology of selective harmonics elimination (SHE) technique suitable for single-phase photovoltaic (PV) tied pulse width modulated (PWM) inverter. Design/methodology/approach: In the proposed SHE, switching angles for inverter control are determined offline through numerical techniques and stored in a microcontroller memory as a function of modulation index (md). The methodology uses the solution that leads to a lower change of switching angles from the previous modulation index (md) for storing in the processor memory for multiple solutions. This leads to a smaller number of sections when a piecewise mixed model is considered for storing the entire switching angle curve for the online inverter control. The proposed idea is simulated and experimentally validated on a laboratory prototype of PV (500 W) grid-tied PWM inverter. The control environment is then realized in NI c-RIO 9082. Findings: This proposed technique is suitable for limiting voltage total harmonics distortion (THD) in single-phase PV tied grid connected voltage source inverter (VSI). Moreover, it is found that filter (L-C) size requirement is less. Originality/value: The proposed SHE with piecewise mixed model technique effectively reduces voltage THD with less filter size (L-C) in a single-phase PV-tied system.